2021
DOI: 10.17216/limnofish.710127
|View full text |Cite
|
Sign up to set email alerts
|

Merzimen Çayı (Fırat Havzası) Garra rufa (Heckel, 1843) Popülasyonuna Ait Yaş ve Büyüme Parametreleri

Abstract: This study was carried out to determine the population parameters of Garra rufa in Merzimen Stream, Euphrates River Basin between May and November 2013. A total of 365 specimens were caught by electro shocker. The age of the sampled specimens ranged from 0 to V age groups. Total length and weight varied from 2.9 to 16.8 cm with a mean of 9.67±3.52 cm and 0.21 to 69.27 g with a mean of 15.69±14.75 g, respectively. The length-weight relationship was obtained as W=0.0124L 2.9888 and the b value indicated the isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The length-weight relation of G. rufa was W=0.038L 2.57 for the females and W=0.011L 2.13 for the males with negative allometry (Student's t-test; p<0.05) (Table 2). G. rufa had positive allometric growth in the most the previous studies (Abedi et al, 2011;Birecikligil and Ciçek, 2011;Hamidan and Britton, 2013;Gerami et al, 2013;Ergüden, 2016;Çiçek et al, 2021). However, we found a negative allometry (b female : 2.57; b male :2.13, Student's t-test; p<0.05) LWR for G. rufa in Göynük Stream, Murat River (Table 2).…”
Section: Resultssupporting
confidence: 39%
“…The length-weight relation of G. rufa was W=0.038L 2.57 for the females and W=0.011L 2.13 for the males with negative allometry (Student's t-test; p<0.05) (Table 2). G. rufa had positive allometric growth in the most the previous studies (Abedi et al, 2011;Birecikligil and Ciçek, 2011;Hamidan and Britton, 2013;Gerami et al, 2013;Ergüden, 2016;Çiçek et al, 2021). However, we found a negative allometry (b female : 2.57; b male :2.13, Student's t-test; p<0.05) LWR for G. rufa in Göynük Stream, Murat River (Table 2).…”
Section: Resultssupporting
confidence: 39%
“…Most of the previous studies of G. rufa (Abedi et al, 2011;Birecikligil & Ciçek, 2011;Hamidan & Britton, 2013;Gerami et al, 2013;Ergüden, 2016;Çiçek et al, 2021) have shown positive allometric growth. However, b coefficient in this study shows negative allometric growth, similar to a few studies (Pazira et al 2013;Segherloo et al, 2015, Keivany & Zamani Faradonbe 2017Aslan et al, 2021) of results from Tigris Basin, Persian Gulf Basin, Zohrer River, Iran and Murat River, Turkey (Table 4).…”
Section: Discussionmentioning
confidence: 94%
“…To date, there is no available data on length-weight and condition data of G. turcica in Turkey. However, only a few studies are conducted on the growth features (Kırankaya et al, 2008;Patimar et al, 2010;Pazira et al, 2013;Aslan et al, 2021;Çiçek et al, 2021) and length-weight relationships for G. rufa by differ researchers (Esmaeili & Ebrahimi 2006;Gerami et al, 2013;Hamidan & Britton, 2013;Keivany & Zamani-Faradonbe, 2017).…”
Section: Discussionmentioning
confidence: 99%